Uso de biossólido como substrate para produção de mudas de eucalipto - De Menezes Trigueiro, Rodrigo [UNESP]; Guerrini, Iraê Amaral [UNESP] (My University, 2003)
The objective of this study was to evaluate the feasibility of the biosolids used as substrate component for seedlings production of Eucalyptus. This way, different proportions of biosolid/carbonized rice (80/20, 70/30, 60/40, 50/05 and 40/60) were tested as substrates in mixture, which were compared to the common substrate used by forest nursery (Multiplant®), as control. The experiment was established with Eucalyptus grandis where growth seedlings-related parameters were assessed: shoot height, collar diameter, accumulation of dry matter on the shoot and root, chemical analysis of the vegetal tissue of aerial part and root, foliar area and chlorophyll content. The results revealed that Eucalypts seedlings developed in substrate with 50% biosolid were similar to the control in relation to the evaluated parameters, concluding that the use of biosolids for seedlings production is quite promising.
Use of biosolids as substrate for Eucalyptus seedlings production
Keywords: Biosolid; Eucalyptus grandis; Nursery; Seedlings; Substrate; Chemical analysis; Chlorophyll; Crops; Forestry; Seed; Substrates; Biosolids; Plants (botany)